PKM. PELATIHAN LITERASI DIGITAL PADA SISWA SEKOLAH DASAR DI KELURAHAN PENATIH KOTA DENPASAR - I Made Subrata; I Wayan Citrawan; I Dewa Putu Juwana; Ni Made Pira Erawati (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
In the 21st century, many people are looking for learning materials using digital media, including teachers and students. Therefore, digital literacy plays an important role in optimizing the use of digital media in providing additional study guidance to catch up with students in learning the material to be studied. However, there are still many students who have not been able to apply the benefits of digital literacy in increasing their ability to absorb learning material. The aim of this service is to improve the digital literacy skills of fifth grade students at State Elementary Schools in the Penatih sub-district. The problem that was agreed upon by the school principal after the PKM Team from PGRI Mahadewa Indonesia University which was deemed necessary to immediately find a solution was the need to increase student knowledge about school digital literacy skills among students. Implementation of digital literacy training at state elementary schools in Penatih Village, East Denpasar District, Denpasar City. The activities carried out have been planned and structured into six stages, namely preparation, assessment, tutoring, mentoring, implementation and evaluation. There are two main types of activities carried out. (1) Learning training activities for students who have difficulty understanding learning material due to the impact of the pandemic. (2) Mentoring activities in providing knowledge about digital literacy to students. After all stages of the activity have been carried out, students who experience material setbacks can catch up again well. With digital literacy training activities, the results show that students' ability to utilize digital media is getting better.